A Coumarin–based Colorimetric and Fluorescent Chemosensor for the "Naked–eye" Detection of Fluoride ion in 100 % Natural Water Medium Using Coated Chromatography Plates. Issue 15 (16th September 2016) - Ren, Xianxuan; Wang, Yue; Meng, Qingtao; Jia, Hongmin; Wang, Yongfei; Kong, Xiangfeng; Duan, Chunying; Zhang, Zhiqiang
Abstract: Based on coumarin dye, a novel colorimetric and fluorescent dual‐modal chemosensor (CL ) was designed and synthesized for fluoride ion (F – ) sensing. The spectroscopic response ofCL towards F – could be attributed to the F – ‐triggered multi‐hydrogen bond interaction. Job's plot analysis indicates thatCL forms a 1:1 stoichiometry complex with F – . The association constant ( K a ) was evaluated using the Benesi–Hildebrand method and was found to be 1.986 × 10 3 M −1 . The fluorescence detection limit for F – was estimated to be 1.5 ppb based on a 3 σ /slope.CL could be easily prepared asCL ‐coated chromatography plates to "naked‐eye" detect of F – in different natural water samples at a low detection limit of 1 ppm . Abstract : A novel fluoride–specific colorimetric and fluorescent chemosensor (CL ) has been developed based on coumarin dye. For the application of fluoride ion detection in the environmental field, theCL ‐coated chromatography plates are also developed and have been successfully used for the "naked‐eye" detection of fluoride ion in different natural water samples at a low limit about 1 ppm .